Teachers' Challenges in Teaching English in Rural School: Case Study at MTs Rubath Naqsyabandiyah Kubu Raya West Kalimantan - Muhammad Siroji; Mulis (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
English, as an international language, plays a significant role in education, especially in preparing students to face global challenges. However, the teaching of English in rural schools still faces several obstacles that affect the effectiveness of learning. This study aims to identify and analyze the challenges faced by English teachers at MTs Rubath Naqsyabandiyah, a school in a rural area. The study uses a qualitative approach with a case study method, where data is collected through classroom observation and in-depth interviews with English teachers. Data analysis follows the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study show several main challenges in teaching English, including low student interest in the subject, lack of support from parents and the surrounding community, teachers' perceived low quality, and high administrative and curriculum burdens. Students in rural areas often fail to see the relevance of English learning to their everyday lives, which reduces their motivation to learn. Additionally, the lack of support from parents worsens the challenges that teachers face in teaching English in these schools. To address these challenges, the study provides several recommendations aimed at improving the effectiveness of English teaching in rural schools. First, increasing student interest by developing fun and relevant teaching methods that connect English to daily activities, local culture, and regional potential. Second, involving parents in supporting their children's English language learning.